2020
DOI: 10.1002/mp.14435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motion and b‐value on apparent temperature measurement by diffusion‐based thermometry MRI: eye vitreous study

Abstract: Purpose: To make noninvasive measurements of temperature in the posterior chamber (vitreous) of the eye using diffusion-based thermometry (DBT) magnetic resonance imaging (MRI) and to explain variability in these measurements due to choice of b-value and the effects of motion. Methods: Phantom studies of human vitreous and distilled water were performed using b-values from 0 to 1500 s/mm 2 to determine the liquid-specific calibration factor for vitreous as well as to determine the temperature offsets due to sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In repeated intraindividual ocular temperature measurements by Derakhshan et al 20 using essentially the same DWI thermometry as ours, they reported an error of up to 7.8°C. Temperature overestimation was observed at the peripheral of the eye in their measurement.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In repeated intraindividual ocular temperature measurements by Derakhshan et al 20 using essentially the same DWI thermometry as ours, they reported an error of up to 7.8°C. Temperature overestimation was observed at the peripheral of the eye in their measurement.…”
Section: Discussionsupporting
confidence: 71%
“…18,19 Furthermore, this method has also been applied to the measurement of vitreous temperature in the eye. 20 One unresolved issue in DWI thermometry has been the potential influence of CSF pulsations, which could affect the larger flow speed compared with the normal magnitude of water diffusion. For instance, jet flow at the foramen of Monro might lead to errors in calculating temperatures in the LV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation